Facebook: o Dionisíaco em uma modulação da forma social - Tavares, Rafael Ramos Pedreira (2013)
This paper is about the form of social modulation, The Facebook. The social order is the form that all parties. The modulations (there are several) are aspects of social order and therefore capable formant. The Facebook, then, is searched as a Dionysian aspects of the social form that appears with cyberculture and the mass consumption. Thus, it is to display the attitude of Dionysian that consume otherness and give up the KEYWORDS: social form, modulation, Dionysian, cyberculture, Facebook consumption on Facebook